(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2009)
The paper is divided into two parts. In the first one, an author analyses her changing position in the field, highlighting a gender and maritial status. Positionality not only gives various access to interlocutors but also defines or even determines her subjects of research. In the second part of a text, a discourse on Torbeshi / Macedonian Muslims is analysed. An author observes, this group is exposed to strong propaganda from Turkish, Albanian and Macedonian perspectives. She argues, this propaganda is also grown by Macedonian scholars for whom Torbeshi are Macedonians who converted into Islam during Ottoman Empire, while there are very few research on their own changing and fluid identification.